Results of the CAPPS: COPD – Assessment of Practice in Primary Care Study. (24th May 2013) - Belletti, Daniel; Liu, Jia; Zacker, Christopher; Wogen, Jenifer
Abstract: Objective: Since many patients with COPD in the US are managed by primary care physicians, we evaluated adherence to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines in a primary care setting. Methods: A cross-sectional study was conducted using a random sample of patients ( n = 50–150 per site) aged 40–89 years with diagnosed COPD. Patients were identified for study inclusion ( N = 1517) from 11 US primary care sites. Demographic and clinical information was extracted from primary care medical records via retrospective chart review. The main outcome measures were adherence to GOLD primary care guidelines, assessed via three components as follows: 1. Is there a current diagnostic spirometry test measurement available within the patient's medical record during the prior calendar year? 2. Are comorbid conditions, if present, being treated appropriately? 3. Are adequate risk reduction measures being taken? Results: Mean patient age was 67.2 (SD ± 11.3) years, 54% were female, and 34% were current smokers. Overall, 19% of patients had comorbid asthma, 66% hypertension, 61% dyslipidemia, 30% cardiovascular disease, and 28% diabetes. Mean duration of COPD was approximately 4.8 years. Only 27% of patients had a spirometry test result documented within the past year. More than half (52%) of patients did not have a documented COPD stage; 20% were classified as stage I, 13% stage II, 12% stage III, 3% stage IV. About 63% of patients met at least one guideline component, while only 3% of patients met all components; 27% met diagnostic, 25% comorbid conditions management, and 32% met risk reduction criteria. Limitations: The retrospective design of our study did not allow evaluation of some possible covariates or causal assessment, and spirometry measurements were unavailable for many patients. Conclusions: Results suggest that treatment per COPD primary care guidelines was not consistently applied among participating practices (range 0.0%–8.7% for meeting all three components). Educational initiatives may increase primary care providers' knowledge of and adherence to COPD treatment guidelines and recommended patient management strategies.